2013
DOI: 10.1186/1471-2377-13-194
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to anesthetic gases and Parkinson’s disease: a case report

Abstract: BackgroundThe administration of anesthetics determines depression of the central nervous system and general anesthesia by inhalation may cause an environmental pollution of the operating rooms. It may therefore conceive a possible occupational etiology of Parkinson's Disease (PD).Case presentationIn a Caucasian male aged 59 years, PD was diagnosed by brain scans with a presynaptic radioactive tracer of the dopaminergic system. Family history was negative for Parkinson’s disease or essential tremor. He was a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…tau hyperphosphorylation) 10 , 11 , 13 , 15 , 16 and induce the aggregation of disease-related proteins (i.e. amyloid and huntington protein) 13 , 15 , 16 , 20 but causal studies in patients have more mixed results 3 , 6 , 7 , 18 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…tau hyperphosphorylation) 10 , 11 , 13 , 15 , 16 and induce the aggregation of disease-related proteins (i.e. amyloid and huntington protein) 13 , 15 , 16 , 20 but causal studies in patients have more mixed results 3 , 6 , 7 , 18 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…86 On the other hand, exposure of presymptomatic AD mice to anesthetics (halothane, isoflurane) did not accelerate the progression of the disease but, on the contrary, appeared to result in the preconditioning against neurodegeneration, due to increased phosphorylation of tau. 87 Despite anecdotal and some epidemiological evidence of a link between anesthetics and AD, 88 PD, [89][90][91] and POCD, 92 clinical evidence does not, on the whole, support the animal studies. Large studies such as the ISPOCD 93 as well as metaanalyses 94,95 have found no link between anesthetics and POCD or AD, including comparisons between general and regional anesthetics.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 97%
“…Halothane and isoflurane increase cytotoxicity by increasing oligomerization of beta-amyloid. The same mechanism presents itself at the nigro-striatal level, producing dopaminergic neurotoxicity (13).…”
Section: Discussionmentioning
confidence: 97%
“…Occupational exposure to anesthetic gases may cause a two-fold increase in the risk of PD. A study comparing mortality from PD showed a statistically significant predominance in anesthesiologists compared to internists (13).…”
Section: Introductionmentioning
confidence: 99%